2017
DOI: 10.1080/17435390.2017.1391344
|View full text |Cite
|
Sign up to set email alerts
|

Brood pouch-mediated polystyrene nanoparticle uptake during Daphnia magna embryogenesis

Abstract: Nanoplastic debris is currently expected to be ubiquitously distributed in aquatic environments and an emerging environmental issue affecting organisms across trophic levels. While ingestion of particles receives most attention, other routes of uptake and cellular accumulation remain unexplored. Here, the planktonic filter feeder Daphnia magna was used to track routes of uptake and target tissues of polystyrene nanoparticles (PSNPs). A sublethal concentration of 5 mg L À1 fluorescent PSNPs (25 nm) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 34 publications
6
42
0
Order By: Relevance
“…However, this was rare and always in the context of a damaged gut, which was probably caused by the sample handling. Brun et al () made a similar observation in daphnids exposed to 25 nm polystyrene beads and attributed particles outside the gut to damage during sample preparation.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…However, this was rare and always in the context of a damaged gut, which was probably caused by the sample handling. Brun et al () made a similar observation in daphnids exposed to 25 nm polystyrene beads and attributed particles outside the gut to damage during sample preparation.…”
Section: Resultsmentioning
confidence: 75%
“…When exposing Daphnia galeata to 5 mg L -1 of 51 nm green fluorescent polystyrene beads, Cui et al (2017) showed fluorescence inside embryos and lipid droplets and concluded that there is a link to the observed toxicity. Brun et al (2017) investigated the brood pouch of D. magna as a potential exposure pathway for embryos, a mechanism proposed by Rosenkranz et al (2009). They © 2019 SETAC wileyonlinelibrary.com/ETC FIGURE 3: Identical Daphnia magna individuals exposed to 1000 nm polystyrene particles for 24 h before (A) and after (B) 60 min of confocal laser scanning microscopy imaging.…”
Section: Dye Leaching Experiments (Experiments 4)mentioning
confidence: 99%
“…These then shot into the blood flow and we found them throughout the body, in fatty organs and tissues and even in the eyes (Van Pomeren et al, 2017). The neonates within the brood pouch of pregnant water fleas were shown to be covered by fluorescently dyed nanoparticles (Brun et al, 2017). From another study (Cui et al, 2017) it could be concluded that when a pregnant female is exposed to nanomaterials, the offspring get off to a difficult start in life.…”
Section: The Dance Of the Nanomaterialsmentioning
confidence: 99%
“…In particular, particle size is known as a crucial factor to govern the properties and performance [13][14][15][16][17][18][19][20]. To measure nanoparticle size, dynamic light scattering is currently used most widely because of the experimental simplicity and automatized data analysis scheme using the instruments developed in compact type [21][22][23][24][25][26]. However, dynamic light scattering very often provides unrealistically large size and distribution [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%